Financial Literacy To Create A Bright Future - Peter, Peter; Hadianto, Bram; Raihin, Yusuf Osman; Aribowo , Agus; Tan , Ming Kuang (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
This service to the community aims to prove the effectiveness of financial literacy substances delivered, i.e., financial, investment, and retirement planning, to the related people in Badan Pendidikan Kristen (BPK) Penabur Metro in Lampung Province. This is due to their inadequate knowledge, obtained after the Maranatha Christian University team interviewed the chief of BPK Penabur Metro. Furthermore, the questions of Chen and Volpe (1988) are utilized to evaluate the success of this event based on the precise answers (PA). Moreover, their percentage gets statistically compared after and before the material delivery (MD). To deliver materials, the presenters utilize the lecture technique. Besides, the discussion is utilized to answer participants' curiosity about the topics. Based on this statistical examination, the portion of PA after the MD is higher than that before the MD, where the level is 62.45% and 36.58%, respectively. In other words, this service to the community successfully elevates their ability to answer these questions.